BETWEEN EXPECTATION AND PRACTICES OF EDUCATOR CERTIFICATION: WHAT DO WE NEED ? - Ummi Rasyidah (English Study Program University of Pasir Pengaraian, 2016)
To some extend, Indonesian government has launched a program namely certification to improve teachers’ quality. The teacher certification process mandated by the law on teachers and lecturers, was developed and is currently being implemented. This program not only has implications regarding the quality of teaching but also deals with salary increases, professional development and promotion possibilities. Different with other countries which teacher certification is given as a licence to teach, in Indonesian this certification is to ensure teacher’s competence level. As a result, a certified teacher is then entitled to a professional allowance in an amount equivalent to his or her base salary.